2020
DOI: 10.1007/978-3-030-57404-8_18
|View full text |Cite
|
Sign up to set email alerts
|

Responding to KRACK: Wi-Fi Security Awareness in Private Households

Abstract: In this paper, we study the update and security practices of individuals in private households with an exploratory interview study. In particular, we investigate participants' awareness regarding KRACK, a patched key vulnerability in the WPA/WPA2 protocol, and similar vulnerabilities in the context of usage and management scenarios in Wi-Fi networks. We show that while most people are aware of certain dangers, they struggle to address Wi-Fi related vulnerabilities. The findings could prove to be beneficial in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Zeng et al [199] (interview, 𝑛 = 15), suggested how users' vulnerability depends on the level of their privacy knowledge, and pointed out a clear mismatch between the awareness and power of the owner/administrator of the smart home in comparison to other home users. Freudenreich et al [58] (interview, 𝑛 = 16), studied security practices of home users related to Wi-Fi security and found that, although they were mostly aware of the vulnerabilities, they found it difficult to address these issues.…”
Section: Periodmentioning
confidence: 99%
See 2 more Smart Citations
“…Zeng et al [199] (interview, 𝑛 = 15), suggested how users' vulnerability depends on the level of their privacy knowledge, and pointed out a clear mismatch between the awareness and power of the owner/administrator of the smart home in comparison to other home users. Freudenreich et al [58] (interview, 𝑛 = 16), studied security practices of home users related to Wi-Fi security and found that, although they were mostly aware of the vulnerabilities, they found it difficult to address these issues.…”
Section: Periodmentioning
confidence: 99%
“…This is another popular area of research, with 66 papers. Some papers (32) focused majorly on this RQ and others (34) reflected on security and privacy behaviors while discussing other concepts such as privacy concerns, awareness, multi-users issues and related conceptual frameworks [4,47,58,61,63,68,70,84,98,100,103,105,114,116,118,123,126,130,134,135,141,144,146,150,164,167,173,178,181,183,187,188,195,200,202]. Here, we will focus on the 32 papers in the former group.…”
Section: Rq5mentioning
confidence: 99%
See 1 more Smart Citation
“…Although patches are available for both KRACK and FragAttacks, the critical problem is that they are not applicable on every Wi-Fi or IoT device because of factors like resource constraints, deprecated security protocols, expired product support periods, etc. Four years after KRACK first appeared, it is estimated that more than 75 per cent of Wi-Fi enabled devices still remain vulnerable to it [10], [11].…”
mentioning
confidence: 99%
“…Although patches are available for both KRACK and FragAttacks, the critical problem is that they are not applicable on every Wi-Fi or IoT device because of factors like resource constraints, deprecated security protocols, expired product support periods, etc. Four years after KRACK's appearance, it is estimated that more than 75 percent of Wi-Fi-enabled devices still remain vulnerable to it [10], [11].…”
mentioning
confidence: 99%